GLOBAL ENVIRONMENTAL PRIORITIES OF SOCIETY DEVELOPMENT - Vyshnevska, O. M. (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2019)
The main object of the article is to identify the global environmental priorities of the development of society on the partnership basis, also taking into account certain international directions of leveling of environmental threats as well as global warming. The research is based on theoretical substantiation and practical introduction of a systematic approach in implementing the environmental policy of states on the terms of partnership. We determined the core characteristics of global ecological priorities of the society development, global ecological policy, principles of international agreements under the UN Framework Convention on Climate Change, and global goals of sustainable development. We defined the characteristics of a partnership for carrying out ecological policy with the goal of leveling global threats. We determined the possibilities of realizing the systemic approach in the development of society in view of global environmental priorities, ratified international agreements, and global goals of sustainable development. In accordance with the global goals of sustainable development, we generalized the principle courses for implementing environmental measures at different standards. It has been determined that the systematic actions in the implementation of ratified commitments by various state governments require significant changes to internal environmental policy, incentives for all participants to implement the predetermined measures, state incentive policy, and the dissemination of environmental knowledge. We determined that the global environmental priorities of the society development are closely linked with the possibility of introducing an action strategy for reforming to a rational model of consumption and production, which would involve all countries all over the world, considering the development and potential of the states, the progress toward rational development and efficient use of natural resources, and rational use of chemical products and other wastes throughout their life cycle in accordance with internationally agreed principles. All measures must be implemented on the basis of partnership.